Versatile Ni-Ru catalysts for gas phase CO2 conversion: Bringing closer dry reforming, reverse water gas shift and methanation to enable end-products flexibility. (1st May 2022) - Merkouri, Loukia-Pantzechroula; le Saché, Estelle; Pastor-Pérez, Laura; Duyar, Melis S.; Ramirez Reina, Tomas
Graphical abstract: Highlights: NiRu/CeO2 -Al2 O3 and NiRu/Ce0.5 Zr0.5 O2 were tested in three CO2 gas-phase reactions. NiRu/CeAl showed better coke resistance in dry reforming of methane (DRM). Equilibrium CO2 conversion was reached at 350 °C for NiRu/CeAl in CO2 methanation. NiRu/CeAl exhibited impressive stability in CO2 hydrogenation reactions and DRM. Abstract: Advanced catalytic materials able to catalyse more than one reaction efficiently are needed within the CO2 utilisation schemes to benefit from end-products flexibility. In this study, the combination of Ni and Ru (15 and 1 wt%, respectively) was tested in three reactions, i.e. dry reforming of methane (DRM), reverse water–gas shift (RWGS) and CO2 methanation. A stability experiment with one cycle of CO2 methanation-RWGS-DRM was carried out. Outstanding stability was revealed for the CO2 hydrogenation reactions and as regards the DRM, coke formation started after 10 h on stream. Overall, this research showcases that a multicomponent Ni-Ru/CeO2 -Al2 O3 catalyst is an unprecedent versatile system for gas phase CO2 recycling. Beyond its excellent performance, our switchable catalyst allows a fine control of end-products selectivity.